Can BPA Analogs Affect Cellular and Biochemical Responses in the Microalga Phaeodactylum tricornutum Bohlin? - Jacopo Fabrello; Maria Ciscato; Emanuela Moschin; Francesca Dalla Vecchia; Isabella Moro; Valerio Matozzo (MDPI AG, 2023)
Bisphenol A analogs (BPA analogs) are emerging contaminants with a rising production caused by the replacement of BPA with these compounds. The increased production of BPA analogs is leading to their increased release into various ecosystems, including marine ones. The aim of this study was to evaluate the biological effects of BPA analogs on a primary producer, the diatom Phaeodactylum tricornutum Bohlin. Three different BPA analogs (BPAF, BPF, and BPS) and their mixture were tested at the environmental relevant concentration of 300 ng/L. Growth, cell size and several biomarkers of oxidative stress and oxidative damage were measured. Our results indicated that the tested compounds caused a reduced growth rate and induced oxidative stress, altering many antioxidant enzymes in P. tricornutum. However, no oxidative damages were observed.